2023
DOI: 10.3390/biomedicines11030777
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Profile Changes in Patients with Gallbladder Stones after UDCA/CDCA Treatment

Abstract: Background: Ursodeoxycholic acid (UDCA) and chenodeoxycholic acid (CDCA) are used to treat patients with asymptomatic or mildly symptomatic gallstone disease. This study was conducted to evaluate the efficacy of gallbladder (GB) stone dissolution by UDCA/CDCA and the impact of treatment on gut microbial profiles. Methods: Fifteen treatment-naive patients with GB stones were initially included, but two dropped out during the treatment period. UDCA/CDCA was administered for 6 months. Abdominal ultrasonography wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Excessive xanthin can cause hyperuricemia and then lead to NAFLD and NASH (Nishikawa et al, 2020). CDCA can be converted into secondary bile acids, such as deoxycholic acid (DCA), and regulate intestinal flora including Faecalibacterium, Roseburia, and Lachnospira, thus, interfering with NASH (Jiao et al, 2018;Lee et al, 2023). In our experiment, SA can maintain the metabolic balance by regulating metabolites such as xanthine, CDCA, and 3a,7a,12a-Trihydroxy-5b-cholestan-26al etc.…”
Section: Discussionmentioning
confidence: 79%
“…Excessive xanthin can cause hyperuricemia and then lead to NAFLD and NASH (Nishikawa et al, 2020). CDCA can be converted into secondary bile acids, such as deoxycholic acid (DCA), and regulate intestinal flora including Faecalibacterium, Roseburia, and Lachnospira, thus, interfering with NASH (Jiao et al, 2018;Lee et al, 2023). In our experiment, SA can maintain the metabolic balance by regulating metabolites such as xanthine, CDCA, and 3a,7a,12a-Trihydroxy-5b-cholestan-26al etc.…”
Section: Discussionmentioning
confidence: 79%
“…Other side, SPBs, such as UDCA, DCA and especially LCA, were decreased under high-sucrose condition. UDCA, usually is used for treating cholestatic liver disease with its ability to promote the secretion of bile aids 44 . Recently, a famous study found that UDCA could protect from SARS-CoV-2 infection by reducing ACE2 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These aspects were also associated with an important increase in the secondary BAs from the enterohepatic cycle. The authors suggested that some bacteria, such as Ruminococcus gnavus spp., could even be used as biomarkers to point to the group that is exposed to GS formation [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%